Characteristics of a sintered porous Ni–Cu alloy cathode for hydrogen production in a potassium hydroxide solution. (15th February 2016) - Yu, Linping; Lei, Ting; Nan, Bo; Jiang, Yao; He, Yuehui; Liu, C.T.
Abstract: A porous Ni–Cu alloy with a most probable pore size of 2.4 μm and an open porosity over 31.5% was synthesized by step sintering pressed compacts consisted of mixed Ni and Cu powders in a vacuum furnace. The electrocatalytic activity and stability of the fabricated porous Ni–Cu alloy as cathode for the HER (hydrogen evolution reaction) in 6.0 mol/L potassium hydroxide solution were investigated by cathodic current–potential curves, CV (cyclic voltammetry) and EIS (electrochemical impedance spectroscopy) techniques. Results show that the onset potential of the porous Ni–Cu for HER greatly shifts to the positive direction compared with the dense Ni and dense Ni–Cu alloy. The electrochemical activation energy is determined to be 26.7 kJ mol −1 for the porous Ni–Cu alloy, against 44.1 kJ mol −1 and 32.6 kJ mol −1 for the dense Ni and dense Ni–Cu alloy, respectively. The increased activity of the porous Ni–Cu alloy for HER is related to the micro-porous structure as well as synergistic interaction of Ni and Cu. Besides, the fabricated porous Ni–Cu alloy displays good corrosion resistance in potassium hydroxide solution during the immersion test, which makes it possible for long-time running as cathode in the process of hydrogen evolution reaction. Highlights: A porous Ni–Cu alloy cathode is conveniently fabricated by powder metallurgy. The porous Ni–Cu cathode shows excellent electro–catalytic activity and stability during HER. The synergistic effect between Ni and Cu can be used to explain the high activity of porous Ni–Cu alloy. The micro-sized porous structure of the cathodes is beneficial for the long-term stability and operation.